The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
International Heat Transfer Conference 16 2018
DOI: 10.1615/ihtc16.kn.000009
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling in Micro-Passages: Developments in Fundamental Aspects and Applications

Abstract: Flow boiling in mini to micro passages located at the heat source, and as part of a thermal management system, has been identified as a possible way to remove the increasing high heat fluxes generated by high power electronic devices due to their capability of high heat transfer rates with small surface temperature variations. However, some still unresolved fundamental issues hinder the possible full adoption of this technology. These relate to the prevailing flow patterns, heat transfer rates and pressure dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Interface sharpening is very important in simulating two-phase flows of two immiscible fluids. In OpenFOAM the sharpening of the interface is achieved artificially by introducing the extra compression term ∇ • (α(1 − α)U ⃗ ⃗ r ) in Equation (4). U ⃗ ⃗ r is an artificial compression velocity.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interface sharpening is very important in simulating two-phase flows of two immiscible fluids. In OpenFOAM the sharpening of the interface is achieved artificially by introducing the extra compression term ∇ • (α(1 − α)U ⃗ ⃗ r ) in Equation (4). U ⃗ ⃗ r is an artificial compression velocity.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The main reason for this, is the lack of accurate design correlations as well as the lack of understanding of several underpinned principles and mechanisms. Karayiannis and Mahmoud [4] recently reported that there are still open fundamental research aspects and issues. One of these is the effect of the solid surface characteristics on the underpinned bubble dynamics and heat transfer.…”
Section: Introductionmentioning
confidence: 99%